The Ambient Politics of Affective Computing - Angela Xiao Wu (Public culture, 2022)
Much attention to affective computing has focused on its alleged ability to “tap into human affects,” a trope also foundational to broader theorizations about big‐data surveillance. What remains understudied and undertheorized is affective computing's social life, where interested parties contest and collude on its deployment. This essay traces how such portable technologies as sentiment analysis and “like” buttons wound up redefining collective action in China, which partly explains the conservative turn observed in Chinese online cultures since the mid‐2010s. It unpacks affective computing's ambient politics — the fraught processes whereby social actors aggressively repackage, reinterpret, and remediate these technologies to fit their agendas, changing social standards for denoting emotions along the way. This essay calls to reorient critical analysis of affective computing away from its design epistemics to its ambient politics and, in parallel, to shift the focus from interiorized subjects to conditions of collective existence.